The Effect of Diversification Strategy and Implementation of Good Corporate Governance on Firm Value - Maria Lusiana Yulianti; Hendri Maulana (DINASTI RESEARCH, 2021)
This study aims to determine the effect of diversification strategy, good corporate governance implementation on firm value. The study consisted of 41 companies were classified as companies withthe most trusted companies category in Indonesia in 2015 by SWA magazine. The analysis technique used is multiple regression analysis and testing using SPSS for Windows version 22 and also test the classical assumption of normality test, autocorrelation test, multicollinearity test and heteroskedastisitas test. The results of this study show that (1) better implementation of the diversification strategy did not result in a significant increase to the company’s firm value, (2) better implementation of good corporate governance, will increase the company’s firm value.